A new consultation, Assessment and reflection model (CARM) used in child and adolescence mental health services (CAMHS). (October 2021) - Mansell, Louise; Hughes, Kirsty; Heyes, Jane-Ward; Brownlee, Adrian; Charm, Clare; Blake, Daniel; Collinge, Sarah; Smith, Jason
UK National Guidelines stress the importance of reducing waiting times for mental health assessments and interventions for children. They stress the importance of early help, multidisciplinary working, and collaboration with families regarding treatment plans. We piloted a new assessment model (CARM) within a CAMHS service to: reduce non-attendance rates and subsequently waiting times; increase staff and patient satisfaction; and improve the quality of assessment. All waiting list patients and new referrals over a three-month period were contacted to self-book an hour session to meet two clinicians who utilised collaborative reflection and formulation to produce a care plan (CARM). Results revealed that non-attendance rates dropped from 33% over the month prior to CARM to 7% during CARM. Satisfaction levels were high. Qualitative feedback regarding satisfaction revealed the most common themes was feeling listened to and having the opportunity to listen to staff reflections. The themes of staff satisfaction included 'feeling more supported' and 'feeling safer in their decision making'. All assessments were completed in the one appointment. A formulation-driven care plan was developed and discussed with the family. This approach has the potential to make services more effective, efficient and satisfying for both staff and families.